2015
DOI: 10.1007/s00414-015-1170-x
|View full text |Cite
|
Sign up to set email alerts
|

A segment of rbcL gene as a potential tool for forensic discrimination of Cannabis sativa seized at Rio de Janeiro, Brazil

Abstract: Cannabis sativa, known by the common name marijuana, is the psychoactive drug most widely distributed in the world. Identification of Cannabis cultivars may be useful for association to illegal crops, which may reveal trafficking routes and related criminal groups. This study provides evidence for the performance of a segment of the rbcL gene, through genetic signature, as a tool for identification for C. sativa samples apprehended by the Rio de Janeiro Police, Brazil. The PCR amplified and further sequenced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Pairwise alignment of C. sativa with other members of the family Cannabaceae showed that C. sativa rbcL sequences were always distinct from other members, including the closely related genus, Humulus. Furthermore, previous studies showed that rbcL sequence analyses could even distinguish between different C. sativa strains (21). To verify these findings, we constructed a network of sand flyderived C. sativa rbcL haplotypes that confirmed them to be reliably species-specific (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Pairwise alignment of C. sativa with other members of the family Cannabaceae showed that C. sativa rbcL sequences were always distinct from other members, including the closely related genus, Humulus. Furthermore, previous studies showed that rbcL sequence analyses could even distinguish between different C. sativa strains (21). To verify these findings, we constructed a network of sand flyderived C. sativa rbcL haplotypes that confirmed them to be reliably species-specific (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Marijuana (Genetic and/or Proteomic Analyses):2016 13-loci STR multiplex method to accurately genotype 199 Cannabis sativa samples from 11 U.S. Customs and Border Protection seizures [ 698 ]; loop-mediated isothermal amplification DNA -based assay for the identification of c. sativa [ 699 ]; rbcL gene for genetic discrimination of seized c. sativa [ 700 ]; comparison of three DNA markers for the detection of male genotype in industrial hemp and medicinal cannabis plants [ 701 ]; review of genetic and genomic tools for cannabis sativa [ 702 ]; RNA-Seq analysis for phenotypic differentiation of fiber-type and seed-type cannabis [ 703 ]; analysis of the nuclear genomic diversity among 340 Cannabis varieties, including fiber and seed oil hemp, high cannabinoid drug-types, and feral population [ 704 ]; analysis of DNA extracted from seed embryos used for individualization of four hemp and six marijuana varieties [ 705 ]; review of genetic resources available for phenotype tracking of cannabis [ 706 ]; 2017 high resolution melting SNP protocol for differentiation of drug and non-drug cannabis plants [ 707 ]; genotyping of 154 individual plants from 20 cultivars for identification of genetic clusters [ 708 ]; restriction fragment length polymorphism of the THCA synthase gene for differentiation of Cannabis subspecies [ 709 ]; 13 loci STR system for forensic DNA profiling of marijuana samples (validated according to relevant ISFG and SWGDAM guidelines) [ 710 ]; loop-mediated isothermal amplification assay for identifying the drug-type strains of C. sativa [ 711 ]; detection and partial characterization of a 16srix-c phytoplasma associated with hemp witches’-broom [ 712 ]; genetic determination of Cannabis sativa var. indica based on six genomic SSRs for genotyping 154 individual plants from 22 cultivars to determine intra-varietal diversity [ 708 ]; 2018 Phylogenetic analysis of samples from four different sites: 21 seizures at the US-Mexico border, Northeastern Brazil, hemp seeds purchased in the US, and the Araucania area of Chile, to determine population substructure using autosomal and lineage markers [ 713 ]; genetic characterization of hemp [ 714 ]; method for extracting DNA from cannabis resin based on the evaluation of relative PCR amplification ability [ 715 ];…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…The DNA method appears to have higher resolution for the individualization of C. sativa plants compared to the other techniques ( Gilmore et al, 2006 ). Since 1990s, various DNA markers were developed and evaluated for the purpose of C. sativa identification, including random amplified polymorphic DNA (RAPD), sequence characterized amplified region (SCAR), DNA barcoding, short tandem repeats (STRs) and single nucleotide polymorphisms (SNPs) ( Hsieh et al, 2003 ; Techen et al, 2010 ; Rotherham and Harbison, 2011 ; Mello et al, 2016 ; Soorni et al, 2017 ; Roman et al, 2019 ). PARD and SCAR genetic markers can identify only the species and sex of C. sativa , and DNA barcoding can accurately identify C. sativa from its adulterants, while none of them can be used for C. sativa individualization or origin inference.…”
Section: Introductionmentioning
confidence: 99%